Clostridium difficile exosporium cysteine-rich proteins are essential for the morphogenesis of the exosporium layer, spore resistance, and affect C. difficile pathogenesis - Calderón-Romero, Paulina (PLoS Pathog, 2018)
Clostridium difficile is a Gram-positive spore-former bacterium and the leading cause of nosocomial antibiotic-associated diarrhea that can culminate in fatal colitis. During the infection, C. difficile produces metabolically dormant spores, which persist in the host and can cause recurrence of the infection. The surface of C. difficile spores seems to be the key in spore-host interactions and persistence. The proteome of the outermost exosporium layer of C. difficile spores has been determined, identifying two cysteine-rich exosporium proteins, CdeC and CdeM. In this work, we explore the contribution of both cysteine-rich proteins in exosporium integrity, spore biology and pathogenesis. Using targeted mutagenesis coupled with transmission electron microscopy we demonstrate that both cysteine rich proteins, CdeC and CdeM, are morphogenetic factors of the exosporium layer of C. difficile spores. Notably, cdeC, but not cdeM spores, exhibited defective spore coat, and were more sensitive to ethanol, heat and phagocytic cells. In a healthy colonic mucosa (mouse ileal loop assay), cdeC and cdeM spore adherence was lower than that of wild-type spores; while in a mouse model of recurrence of the disease, cdeC mutant exhibited an increased infection and persistence during recurrence. In a competitive infection mouse model, cdeC mutant had increased fitness over wild-type. Through complementation analysis with FLAG fusion of known exosporium and coat proteins, we demonstrate that CdeC and CdeM are required for the recruitment of several exosporium proteins to the surface of C. difficile spores. CdeC appears to be conserved exclusively in related Peptostreptococcaeace family members, while CdeM is unique to C. difficile. Our results sheds light on how CdeC and CdeM affect the biology of C. difficile spores and the assembly of the exosporium layer and, demonstrate that CdeC affect C. difficile pathogenesis.